Translanguaging in EFL Classroom at A Private University in South Sulawesi - Satriyana Muis; Kisman Salija; Sahril Nur; Geminastiti Sakkir (PT ARRUS Intelektual Indonesia, 2023)
This research aims to investigate translanguaging in an EFL classroom. Several researchers have researched translanguaging (1) Sahib (2019), (2) Saputra (2014), (3) Rabbidge (2019), Yuvayapan (2019), Aoyama (2020), and Rasmin & Nur (2023). Nevertheless, in south Sulawesi, especially Palopo still not enough. Hence, this research tries to see the practice of translanguaging in EFL classrooms. This research focused on exploring the reasons lecturers conduct translanguaging, the way lecturers conduct translanguaging in EFL classrooms, and the lecturers’ and students’ perceptions toward translanguaging. The participants of this research were two English lecturers and fifteen students in the fourth-semester English education department at Cokroaminoto Palopo University. This research applied a qualitative method, the instruments were classroom observation and interview. The result of the observation and interview was transcribed and analyzed based on the research focus. The findings of this research were the reasons lecturers conducted translanguaging the first to make their English teaching in the classroom effective and the second to make the students understand the teaching and learning material well. The way lecturers conduct translanguaging is based on the situation of the students. If the students do not understand what the lecturers explain in English, they will use translanguaging in the classroom to make the teaching and learning process run smoothly. The lecturers express a positive perception toward translanguaging which is reflected through ten positive comments about the use of translanguaging in the EFL classroom. The students also give a positive perception of the five questions that have been asked. The students can feel the benefit of the use of translanguaging in the EFL classroom.